2013
DOI: 10.1292/jvms.13-0251
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Diversity of Merozoite Surface Antigen 1 (MSA-1) among <i>Babesia bovis</i> Detected from Cattle Populations in Thailand, Brazil and Ghana

Abstract: In the present study, we screened blood DNA samples obtained from cattle bred in Brazil (n=164) and Ghana (n=80) for Babesia bovis using a diagnostic PCR assay and found prevalences of 14.6% and 46.3%, respectively. Subsequently, the genetic diversity of B. bovis in Thailand, Brazil and Ghana was analyzed, based on the DNA sequence of merozoite surface antigen-1 (MSA-1). In Thailand, MSA-1 sequences were relatively conserved and found in a single clade of the phylogram, while Brazilian MSA-1 sequences showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Cattle, as well as buffaloes, have been screened with highly sensitive PCR assays to detect persistently infected animals in order to genetically characterize the Merozoite Surface Antigen (MSA-1) diversity in Babesia bovis populations present in cattle premises from Mexico [20], Thailand, Brazil and Ghana [21], Vietnam [22], Thailand [23], Sri Lanka, Mongolia and Vietnam [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle, as well as buffaloes, have been screened with highly sensitive PCR assays to detect persistently infected animals in order to genetically characterize the Merozoite Surface Antigen (MSA-1) diversity in Babesia bovis populations present in cattle premises from Mexico [20], Thailand, Brazil and Ghana [21], Vietnam [22], Thailand [23], Sri Lanka, Mongolia and Vietnam [24].…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic polymorphism has been applied as a strategy by most protozoan parasites to escape the immune response of mammalian hosts, and it is a major obstacle preventing the development of effective vaccines against these parasites [7]. In our present study, analysis of the genetic relationships of B. bovis MSA-1, MSA-2b and MSA-2c of Chinese isolates, with respect to almost all available related sequences deposited in the GenBank database (including Mongolia, Vietnam, Philippines, Thailand, Israel, Vietnam, Sri Lanka, Mexico, Argentina, Brazil, Japan and USA) was conducted [7,12,[18][19][20][21][22][23][24]26,30,31]. Phylogenetic analysis showed that the MSA-1 amino acid sequences had a wide distribution in four clades.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses of B. bovis MSAs have been performed in several countries, including Mongolia, Vietnam, the Philippines, Thailand, Israel, Vietnam, Sri Lanka, Mexico, Argentina and Brazil [7,12,[18][19][20][21][22][23][24][25][26]. In China, molecular epidemiological investigations of B. bovis infection have been performed in several provinces [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Among those families mentioned above, the rap1 , msa1 , sbp2 , and 6-cys multigene families and their encoded proteins fall into the variable category. The diversity present in variable genes coupled with their relative stability make them good markers for use in epidemiologic studies at the isolate level, and advantage has been taken of rap1 and msa1 sequences repeatedly for this purpose (for example, see [21,22,23,24,25,26,27,28,29,30]). In contrast, members of the ves multigene family are highly variant in sequence and the expressed member(s) further vary rapidly during the course of infection in an individual host [14].…”
Section: Major Variable and Variant Multigene Protein Familiesmentioning
confidence: 99%